Burgund - Droste, Thorsten, 1950-2011; Budeit, Hans Joachim (München : Hirmer Verlag, 1998)
Relaties van Bourgondië met Europese landen - Verschillende plaatsbeschrijvingen
Keywords: Architektur; Burgund